Performance-based seismic design of concrete structures and infrastructures - Plevris, Vagelis, 1976-; Kremmyda, Georgia, 1979-; Fahjan, Yasin, 1967- (IGI Global, 2017)
"This book provides contributions on Earthquake Engineering and on Performance-Based design of concrete structures. This book includes topics such as advanced methods for the seismic assessment and vulnerability of structures, strength-based and deformation-based design, and Numerical Models for the Seismic Assessment of Concrete Structures"-- Provided by publisher.
"Premier reference source" -- book cover.
Keywords: Concrete construction.; Earthquake resistant design.; Buildings -- Performance.; Buildings, Reinforced concrete -- Earthquake effects.; elektronické knihy; electronic books